Efeitos do ambiente e de características funcionais na diversidade e composição de anuros - Cruz, Sâmia Leticia Reolon da (2022)
The species that compose the communities differ between environments, however which characteristics and which environmental variables are associated with these changes are not well established, especially in animals with complex life cycles, such as frogs. Here we demonstrate how frog characteristics, associated with environmental factors, determine changes in species composition and diversity to respond: (i) Is there a species turnover and characteristics between communities? (ii) How might development stages be influencing these changes across communities? and (iii) How environmental variables influence species diversity and distribution? To answer these questions, we sampled 31 sites in Turvo State Park, Rio Grande do Sul, Brazil. In addition, we obtained species morphological and life cycle data from scientific literature. To relate species functional characteristics to environmental variables, we performed taxonomic and functional composition analysis, and then multiple regressions. We found that depth, canopy openness and hydroperiod are the main variables related to taxonomic and functional richness, as well as with species and characteristics turnover in between communities. Moreover, both development stages (i.e. tadpoles and adults) had characteristics related to these main variables and temperature, dissolved oxygen (OD), conductivity, vegetation and area. However, tadpole characteristics are mainly related to depth, canopy openness, and hydroperiod.